2019
DOI: 10.3390/molecules24244627
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Protective Effect of Panax vietnamensis by Heat Processing on Cisplatin-Induced Kidney Cell Toxicity

Abstract: Cisplatin is a platinum-based anticancer agent used for treating a wide range of solid cancers. One of the side effects of this drug is its severe nephrotoxicity, limiting the safe dose of cisplatin. Therefore, many natural products have been studied and applied to attenuate the toxicity of this compound. In this study, we found that steamed Vietnamese ginseng (Panax vietnamensis) could significantly reduce the kidney damage of cisplatin in an in vitro model using porcine proximal tubular LLC-PK1 kidney cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Studies ( Qi et al, 2019 ) have revealed that Rh2 has a protective effect on cisplatin-induced kidney dysfunction and can improve cisplatin-induced renal histopathological damage, inflammatory response, and renal tubular cell apoptosis. In the study of Kim Long Vu Huynh et al ( Vu-Huynh et al, 2019 ), from processed Vietnamese ginseng, they isolated six PPD-type saponins, including ginsenoside Rh2 and ocotillo genin, that displayed the potential to protect the kidney from cisplatin-induced toxicity. In addition, GO, and KEGG pathway analyses revealed that SHD mainly interferes with AKI occurrence and development through TNF and IL-17 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Studies ( Qi et al, 2019 ) have revealed that Rh2 has a protective effect on cisplatin-induced kidney dysfunction and can improve cisplatin-induced renal histopathological damage, inflammatory response, and renal tubular cell apoptosis. In the study of Kim Long Vu Huynh et al ( Vu-Huynh et al, 2019 ), from processed Vietnamese ginseng, they isolated six PPD-type saponins, including ginsenoside Rh2 and ocotillo genin, that displayed the potential to protect the kidney from cisplatin-induced toxicity. In addition, GO, and KEGG pathway analyses revealed that SHD mainly interferes with AKI occurrence and development through TNF and IL-17 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Steamed red and black ginseng exhibited more promising therapeutic potential than non-steamed ginseng (Jin et al, 2015;Vu-Huynh et al, 2019). In 2004, red ginseng was certified as a health functional food by the Korean Health Functional Foods Act (So, Lee, Kim, Hyun, & Han, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 , 7 , 8 ]. Concerning therapeutic value, VG is also proven to possess many interesting biological activities such as being anti-melanogenic, anti-oxidative, anti-stress, anti-cancer, hepato-cytoprotective, and having nephroprotective effects against cisplatin toxicity [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%